Reported infant feeding practices and contextual influences on breastfeeding: qualitative interviews with women registered to MomConnect in three South African provinces - Trafford, Zara; Jewett, Sara; Swartz, Alison; LeFevre, Amnesty E.; Winch, Peter J.; Colvin, Christopher J.; Barron, Peter; Bamford, Lesley (International breastfeeding journal, 2020)
Background Global guidelines recommend exclusive breastfeeding (EBF) for the first 6 months of life. South African EBF rates have steadily increased but still only average 32% for infants below 6 months of age. Malnutrition and developmental delays continue to contribute substantially to the morbidity and mortality of South African children. MomConnect, a national mHealth messaging system used to send infant and maternal health messages during and after pregnancy, has a specific focus on improving rates of breastfeeding and has achieved high rates of population coverage. Methods For this qualitative study, we interviewed women who were registered to MomConnect to investigate their breastfeeding and other infant feeding practices, decision-making pre- and post-delivery, and the role of the health system, family members and the wider community in supporting or detracting from breastfeeding intentions. Data were collected from February–March 2018 in South Africa’s KwaZulu-Natal, Free State and Gauteng provinces. Framework analysis was conducted to identify common themes. Results Most women interviewed had breastfed, including HIV-positive women. Even when women had delivered by caesarean section, they had usually been able to initiate breastfeeding a few hours after birth. Understandings of EBF varied in thoroughness and there was some confusion about the best way to cease breastfeeding. Most women felt well-equipped to make infant feeding decisions and to stick to their intentions, but returning to work or school sometimes prevented 6 months of EBF. Advice from the health system (both via clinics and MomConnect) was considered helpful and supportive in encouraging EBF to 6 months, although family influences could thwart these intentions, especially for younger women. Mothers reported a range of breastfeeding information sources that influenced their choices, including social media. Conclusions Efforts to improve EBF rates must include consideration of the social and economic environment surrounding women. Interventions that focus only on improving women’s knowledge are valuable but insufficient on their own. Attention should also be paid to infant behaviors, and how these affect women’s breastfeeding choices. Finally, although there is strong local policy support for EBF, more rigorous implementation of these and other broader changes to create a more enabling structural environment ought to be prioritized.